Factors influencing low cost housing in Sana’a – Yemen - Wa’el , Alaghbari; A., Salim; A.A.A. , Ali; K. , Dolla (2008)
The Purpose of this study to identify the factors influences housing cost in low cost housing projects in Sana’a the capital of Yemen. A questionnaire survey has been used as the tools to carry out this study. The questionnaire survey consisted of 32 factors which were grouped into five major categories named; land factors, materials used factors, construction methods used factors, finishing works factors and external factors. The level of importance of the categories was measured and ranked the relative importance weights. This study found that land cost factor, cement cost factor and steel cost factor are the most important factors influencing housing cost in Sana’a. Based on the analysis of the ranking and intensity of a housing cost factors, this paper suggests possible improvements that could be made in order to decrease the housing cost.